2017
DOI: 10.1158/1538-7445.sabcs16-p4-22-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-22-03: Palbociclib in combination with endocrine therapy in treatment-naive and previously treated elderly women with HR+, HER2– advanced breast cancer: a pooled analysis from randomized phase 2 and 3 studies

Abstract: Background: At least 40% of breast cancers are diagnosed in women ≥65 y old and most are hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2-). Palbociclib (PAL) is an oral, small-molecule inhibitor of cyclin-dependent kinases 4 and 6. Randomized studies of PAL combined with endocrine therapy (ET) demonstrated significantly improved progression-free survival (PFS) in patients (pts) with treatment-naive and previously treated advanced breast cancer (ABC). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a pooled analysis of data from 872 patients enrolled in the randomized phase II and III studies (PALOMA-1, -2 and -3) investigating safety and efficacy of palbociclib plus letrozole or fulvestrant in ER-positive, HER2-negative breast cancer, 221 (25%) of the participants were aged 65–74 and 83 (10%) were aged 75+. 33 In the first-line setting for all patients, median PFS was 24.4 months (95% CI 22.0–26.2) in the combined palbociclib and letrozole group versus 13.6 months (95% CI 11.1–16.4) in the placebo and letrozole group with an HR of 0.53 (95% CI 0.44–0.64). In the pretreated group, median PFS was 9.5 months (95% CI 9.2–11.0) in the combined palbociclib and fulvestrant group versus 4.6 months (95% CI 3.5–5.6) in the placebo and fulvestrant group with an HR of 0.46 (95% CI 0.36–0.59).…”
Section: Palbociclibmentioning
confidence: 94%
“…In a pooled analysis of data from 872 patients enrolled in the randomized phase II and III studies (PALOMA-1, -2 and -3) investigating safety and efficacy of palbociclib plus letrozole or fulvestrant in ER-positive, HER2-negative breast cancer, 221 (25%) of the participants were aged 65–74 and 83 (10%) were aged 75+. 33 In the first-line setting for all patients, median PFS was 24.4 months (95% CI 22.0–26.2) in the combined palbociclib and letrozole group versus 13.6 months (95% CI 11.1–16.4) in the placebo and letrozole group with an HR of 0.53 (95% CI 0.44–0.64). In the pretreated group, median PFS was 9.5 months (95% CI 9.2–11.0) in the combined palbociclib and fulvestrant group versus 4.6 months (95% CI 3.5–5.6) in the placebo and fulvestrant group with an HR of 0.46 (95% CI 0.36–0.59).…”
Section: Palbociclibmentioning
confidence: 94%
“…36 A pooled analysis of data from elderly patients in the PALOMA-1, -2, and -3 studies showed that palbociclib combined with endocrine therapy versus endocrine therapy alone improved PFS in patients aged 65-74 years (HR 0.66; 95% CI 0.45-0.97; p = 0.0162) and those aged 75 years and over (HR 0.31; 95% CI 0.16-0.61; p = 0.0002). 55 Moreover, findings from the pooled analysis demonstrated no new safety concerns in elderly patients taking palbociclib. 55 Patients with hepatic or renal impairment Palbociclib exposure is not altered in patients with mild hepatic impairment [total bilirubin ⩽ upper limit of normal (ULN) and aspartate aminotransferase (AST) > ULN, or total bilirubin >1.0-1.5 × ULN and any AST] or in patients with mild [60 ml/min ⩽ creatinine clearance (CrCl) <90 ml/min] or moderate renal impairment (30 ml/min ⩽ CrCl <60 ml/min) and therefore does not typically require dose adjustments.…”
Section: Elderly Patientsmentioning
confidence: 89%
“…55 Moreover, findings from the pooled analysis demonstrated no new safety concerns in elderly patients taking palbociclib. 55 Patients with hepatic or renal impairment Palbociclib exposure is not altered in patients with mild hepatic impairment [total bilirubin ⩽ upper limit of normal (ULN) and aspartate aminotransferase (AST) > ULN, or total bilirubin >1.0-1.5 × ULN and any AST] or in patients with mild [60 ml/min ⩽ creatinine clearance (CrCl) <90 ml/min] or moderate renal impairment (30 ml/min ⩽ CrCl <60 ml/min) and therefore does not typically require dose adjustments. 8 Recently, palbociclib has also been studied in patients with moderate or severe hepatic impairment or severe renal impairment.…”
Section: Elderly Patientsmentioning
confidence: 89%